2018
DOI: 10.1093/geronb/gbx156
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Model of Dynamic Markers of the Alzheimer’s Pathological Cascade

Abstract: Our statistically derived models of the AD pathological cascade are consistent with existing theoretical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Therefore, longitudinal approaches are needed to determine the causality. Although the causality order of pulsatility and volume could be alternated, the brain volumetric measure in MRI reveals a relatively early indicator than the severity of cognitive outcomes in AD pathological cascade model ( Balsis et al, 2018 ; Jack et al, 2013 ). Thus, the cerebral pulsatility could also be a sensitive cerebrovascular marker in the relatively early stage of the disease, and therefore helpful to better understanding of early pathophysiological mechanisms of AD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, longitudinal approaches are needed to determine the causality. Although the causality order of pulsatility and volume could be alternated, the brain volumetric measure in MRI reveals a relatively early indicator than the severity of cognitive outcomes in AD pathological cascade model ( Balsis et al, 2018 ; Jack et al, 2013 ). Thus, the cerebral pulsatility could also be a sensitive cerebrovascular marker in the relatively early stage of the disease, and therefore helpful to better understanding of early pathophysiological mechanisms of AD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid‐β (Aβ) and tau accumulation occurs in the forms of amyloid plaques and neurofibrillary tangles in the brain of an AD patient, which is accompanied by neural degeneration and loss (Chételat, 2013; Duan et al, 2016; Wang et al, 2020). The brain alternations due to AD may precede memory impairment, which can be detected by neuroimaging methods (Balsis et al, 2018; Habib et al, 2017; Sun et al, 2016). With the progress of AD research, the focus has gradually shifted to the early stage of the disease, for example, preclinical AD (preAD), which refers to the stage without cognitive impairment (CI) but with abnormal AD biomarkers (Aβ+).…”
Section: Introductionmentioning
confidence: 99%
“…accumulation occurs in the forms of amyloid plaques and neurofibrillary tangles in the brain of an AD patient, which is accompanied by neural degeneration and loss (Chételat, 2013;Duan et al, 2016;. The brain alternations due to AD may precede memory impairment, which can be detected by neuroimaging methods (Balsis et al, 2018;Habib et al, 2017;Sun et al, 2016).…”
mentioning
confidence: 99%
“…The ADNI data set has been a rich source of material for those investigating the value of the AT(N) approach. Despite data-driven models of disease progression10,21,23,[55][56][57][58][59] largely recapitulating the classic temporal sequence of events (i.e., amyloidosis preceding pathologic tau aggregation leading to neurodegeneration), other sequences of biomarker abnormality are possible, such as that found in primary tauopathies in which tau aggregation precedes amyloidosis. A study of ADNI CU and MCI participants that followed trajectories of AT(N) biomarkers found that the biomarker for amyloidosis most commonly became pathological first, and subsequently diverged into a faster-progressing A→T→N evolution and the much slower-progressing A→N→T evolution (FigureS7in supporting information) 60.…”
mentioning
confidence: 99%